An Integrated Design-Based Learning Management Model to Promote Thai Undergraduate Computational Thinking Skills and Programming Proficiency - Prommun, Phattharapol; Kantathanawat, Thiyaporn; Pimdee, Paitoon; Sukkamart, Thanate (My University, 2022)
The study applied concepts of computational thinking, waterfall programming, and design-based learning management (DBLM) combined with a participatory action research (PAR) methodology to obtain an integrated learning management model (LMM) designed as a base to promote computational thinking skills (CTS) and programming proficiency. The study used three groups consisting of 21 volunteer computer education undergraduate students, three teachers, and three computer studies graduates from the Computer Studies Department of the Faculty of Education at Dhonburi Rajabhat University in Thailand. To verify the model, nine educational experts conducted an assessment of the proposed model, and determined that the evaluation standards were overall at a high level (x= 4.23, SD = 0.44), with the experts feeling that the integration of the DBLM computational thinking framework, the Waterfall programming conceptual framework, and the PAR meeting the study's stated objectives at the highest level (x= 4.56, SD = 0.53). The proposed model is best undertaken in five week sessions of five hours each using five exercises per week. Activity effectiveness is best measured by taking notes, worksheets, and practicing the learned skills. In conducting this research, there may be obstacles from learners who may withdraw during research due to personal activities or becoming discouraged in learning activities based on a five-week schedule, preventing them from participating every time.
Keywords: Computational thinking; Design-based learning; Participatory action research; Programming; Thailand